Efektivitas Metode Bernyanyi Dalam Meningkatkan Penguasaan Kosakata Bahasa Arab Di Surabaya: Efektivitas Metode Bernyanyi Dalam Meningkatkan Penguasaan Kosakata Bahasa Arab Di Surabaya - abdullah Sarif; firdausi nurharini (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2022)
The effectiveness of the singing method in improving Arabic vocabulary mastery in class VIII SMP YPP Nurul Huda Surabaya has a background, namely 1) Students have limited vocabulary when speaking Arabic, 3) Difficulty in memorizing vocabulary because teachers still use monotonous methods, 4) Teachers often apply the lecture method so that students have difficulty in understanding the material and memorizing vocabulary. The purpose of this study was to determine how the vocabulary mastery of class VIII students and the effectiveness of using the singing method in improving Arabic vocabulary mastery in class VIII. This type of research is Classroom Action Research with quantitative methods. The subjects of this study were students of class VIII. While the object of the research is class VIII junior high school students, then the data collection techniques that the writer chooses are interviews, observations, and tests. The results of the research before the application of the singing method was that 26% of students had scores in the low and very low categories, after the implementation of the singing method and a Post-Test was held, 81% of students had scores in the high category, so it can be concluded that the singing method is effective for improving mastery. Arabic vocabulary for eighth grade students of SMP YPP Nurul Huda Surabaya.